Modernisasi Pengelolaan Museum sebagai Destinasi Wisata: Studi Kasus Museum House of Sampoerna Surabaya - Eko Tjiptojuwono (HOSPITALITI DAN PARIWISATA, 2019)
The modern museum management is needed to increase the number of tourists visiting the museum. Museum House of Sampoerna is a museum that has been trying to implement a modern museum management so as to change the public's perception of the museum. In general, people have almost the same perception of museums including that the museum was not clean, has a characteristic odor, poor service, facilities are extremely limited, and the museum only be visited once in a lifetime. This study was conducted to determine the extent of the potential of a modern musem if it is managed as a tourist destination in its efforts to attract foreign tourists and domestic tourists with case study on Museum House of Sampoerna, which is as a major tourist destination of Surabaya. The method used in this research is to analyze the data and information obtained from the field research and documentation using SWOT analysis and describe the results of the analysis to the purpose to be achieved by this research. The results showed that the museum House of Sampoerna has tried to make a modern museum management by providing support facilities are modern that can add convenience and attract tourists to visit this museum. Modern facilities provided by the museum house of sampoerna were art gallery, cafe, souvenir shop, public areas for art events, and bus to Surabaya heritage track program. Modern museum management will increase visits to the museum and even tourists will visit more than one time in a lifetime. This study has limitations that the data and information not obtained from all stakeholders of a museum, but only from researcher observation, documentation and interview with the management. Suggested for further research to use visitors as a respondent to represent the public perception of the museum.